ANALISIS DAMPAK LALU LINTAS PADA FASILITAS KESEHATAN EVERGREEN MEDIKA KABUPATEN SORONG - Abdullah, Agus; Desembardi, Faried; Rusmin, Muhammad; Fajar, M. Nur; Rini, Retno Puspa (Eternitas: Jurnal Teknik Sipil, 2024)
Heavy traffic results in vehicles piling up on the shoulder of the road due to the lack of adequate parking space. So it will cause traffic to be disrupted because it only optimizes one lane. Therefore, the Evergreen Clinic building has a big influence on changes in road use, because the Evergreen Clinic does not have a large parking area. This research aims to determine and anticipate the impact of denser traffic around the Evergreen Clinic area. This research examines the traffic impact analysis in terms of traffic loading that occurs due to the existence of the Evergreen Medika Health Facility in Sorong Regency. Where the impact of parking on traffic performance on the roads around the Evergreen Clinic is on average in category C, this can also explain that there is a negative impact, namely congestion due to parking activities on traffic. The effect of parking on traffic performance on the road around the Evergreen Clinic on Sundays and Mondays has a correlation coefficient of 1.00, meaning there is a very strong relationship which indicates that parking activity on Mondays and Sundays has a very strong influence on the traffic volume on the road. Around Evergreen Clinic.